SINUS LIFT PROCEDURES IN UPPER JAW DENTAL IMPLANTOLOGY: TECHNIQUES, INDICATIONS, AND CLINICAL OUTCOMES (International journal of medical sciences, 2026)
This article explores the use of sinus lift procedures in upper jaw dental implantology. Anatomical features of the posterior maxilla, particularly the location of the maxillary sinus and available bone volume, directly influence implant placement and long-term success. The primary aim of sinus lifting is to create sufficient bone height for stable implant insertion, ensure proper osseointegration, and improve prosthetic functionality. The article discusses the two main techniques—lateral window (open) and transalveolar (closed)—as well as various bone grafting materials, including autogenous, allogenic, xenogenic, and synthetic options. Indications, contraindications, potential complications, and risk management strategies are analyzed. Results indicate that sinus lifting enhances implant stability, restores masticatory function, and provides improved aesthetic outcomes while ensuring predictable long-term success. Emphasis is placed on thorough preoperative assessment, precise surgical technique, and careful postoperative management. Overall, sinus lift procedures represent an effective and reliable adjunctive method in upper jaw implantology, expanding treatment options for patients with posterior maxillary bone deficiencies.